Students' Ability to Comprehend English Idioms - Ernida Hamid (AL LUGHAWIYAAT, 2021)
Using English idiomatic expressions fluently is not an easy thing for students of English as a Foreign Language (EFL). Attempts to translate literally from native speakers always lead to confusion and students are often forced to use language that is complex and difficult to comprehend. This research was conducted with the aim of describing students' ability to comprehend English Idioms and the factors that tend to influence the students’ ability to comprehend idioms. The research population was the third year students of language department with census system. The research data obtained by using test and interview. The collected data from the test analyzed by descriptive statistic while the data from  interview were identified to support explanation in relation to students’ ability to comprehend English Idioms. The results of this study showed that the ability of the third-year students of language department to comprehend English idioms and to use in sentences is categorized into insufficient ability. At average the mean of the students’ marks is 4, and the factors which tend to influence the ability of the third year students of language department included students’ internal and external factors. The students’ intenal factor is students  perception on english in general and on English idioms in particular. The students’ external factors are teacher and unavailability of books of English idioms.Keywords: Students ability;English Idioms.